pellet

JP2024511090A5Inactive Publication Date: 2025-02-27BINDING SOLUTIONS LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023558246
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-03-22
Filing Date
2022-03-18
Publication Date
2025-02-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

C-grade iron fines, a byproduct of steel smelting, are difficult to process due to low metallic iron content and high impurity levels, leading to low commercial value and environmental waste disposal issues.

Method used

Formation of pellets using C-grade iron fines and a binder, which can be used as a replacement for scrap metal in steel production, improving purity and reducing environmental pollution.

Benefits of technology

The pellets provide a stable, high-quality alternative to scrap metal, enhancing steel production efficiency and reducing waste, while being economically viable.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

Pellets comprising C grade iron fines and a binder; a method for making said pellets comprising mixing the C grade iron fines and the binder to form a mixture and agglomerating the mixture to form pellets; and a method for making steel comprising heating pellets comprising the C grade iron fines and the binder in an electric arc furnace.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to pellets, particularly iron-containing pellets formed from C-grade fines. [Background technology]

[0002] While abundant in the Earth's core, like all of the Earth's resources, the amount of available iron is finite and environmental costs, particularly in terms of pollution, are associated with iron mining and smelting activities. As a result, it is desirable to maximize the recycling of iron-containing waste materials, which in turn reduces the amount of iron waste that must be disposed of, typically by long-term storage in heaps or ponds.

[0003] Technology exists to process waste iron, such as from scrap metal, into steel. Often the scrap metal is "shredded" (white goods or automobiles, or other light gauge steel) or heavy melt (large slabs of timber) that is processed using electric arc furnaces. The problem with using scrap metal is that the quality of the input steel (and therefore the steel produced) is often poor. As a result, the steel produced from the scrap metal often needs to be upgraded by adding relatively expensive sponge iron or pig iron. This can make recycling such waste material commercially unviable.

[0004] WO 2018 / 193243 describes the production of steel from iron ore in an electric arc furnace, where the iron ore is treated in a reducing atmosphere, thereby producing iron that can be converted into steel at a lower cost than recycling scrap metal using electric arc processing techniques. Summary of the Invention [Problem to be solved by the invention]

[0005] C-grade iron fines are a product of the iron and steel smelting industry. For example, C-grade iron fines are one grade of scrap metal remaining after sorting of air-cooled slag. Produced in large quantities, they are considered waste material, difficult to process, and of low commercial value; because the components present (typically a mixture of iron ore, other metal ores, slag, and iron) are difficult to separate. As a result, while other grades of smelting by-products are typically refined and recycled, C-grade iron fines are typically found as a component of the waste smelting material piles mentioned above.

[0006] This is in part because C-grade iron fines generally contain low amounts of metallic iron, often in the range of 20-40% by weight of the fines, and therefore extracting the iron from the fines has historically been economically impractical. Unlike metallic iron, it has been possible to commercially extract some ferroalloys in amounts as low as 10% by weight. However, it would be desirable to recover this raw iron material, and the present invention is intended to overcome or ameliorate at least some aspects of this problem. [Means for solving the problem]

[0007] Thus, in a first aspect of the present invention, pellets are provided that include C-grade iron fines and a binder. The pellets may be used by the steel industry as a replacement for scrap metal, making efficient use of otherwise wasted resources and helping to reduce environmental pollution caused by the dumping of iron waste. The pellets have been found to provide a more stable product than scrap metal, having fewer impurities (in other words, the pellets are "cleaner" since scrap metal would normally contain contaminants such as oil, plastic, and / or copper), and are less expensive; since the main components of the pellets are essentially cost-free components, since C-grade iron fines have no commercial value. Furthermore, there is an economic advantage to recycling the waste C-grade iron fines as opposed to disposing of them, since the waste can be sold to generate revenue for the manufacturer. This reduces the disposal burden on smelting companies since the amount of waste produced would be significantly reduced. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The term "C grade fines" as used herein is intended to be given its ordinary meaning in the industry. The smelting of iron produces a variety of metallic by-products that are typically classified as A grade, B grade, and C grade. This classification is primarily due to the size of the components; the largest agglomerates form A grade scrap, the smaller (generally less valuable) agglomerates form B grade scrap, and the fines form C grade scrap, which is commonly referred to as C grade fines. Thus, C grade fines is a term that describes granular metallic matter that contains low amounts of other materials. This is in contrast to "dust," which is fine oxidized metal particles, and "tailings," which is a wet particulate slurry containing impurities. Typically, C grade fines have an average particle size in the range of 50 μm to 10 mm, often in the range of 500 μm to 6 mm, and often in the range of 1 mm to 4 mm. The particle size distribution is such that generally 100% of the fine particles will be less than 10mm in average diameter, and often 80-100% of the particles will be less than 6.3mm in average diameter. This differs from many metal powders or dusts which would be expected to have a particle size distribution with a maximum particle size of about 1mm.

[0009] Reference to "C grade iron fines" is intended to include C grade fines containing any metallic iron and / or ferroalloys. C grade iron fines may be unprocessed, in which case they will typically contain metallic iron and / or ferroalloys in the range of 20-40% by weight of the fines, or they may be processed to increase the metallic iron and / or ferroalloy content, for example, to a range of 50-95% by weight of the fines, often 60-85% by weight, or 70-80% by weight of the fines. The amount of iron found in the processed C grade iron fines is such that the pellets are an excellent, cheap and clean alternative to ferrous scrap metal sources.

[0010] The terms "iron" and "metallic iron" are used interchangeably herein, and the term "ferroalloy" has its ordinary meaning in the art, specifically, ferroalloys are alloys of iron with a high percentage of one or more other elements (the largest percentage, but often less than 50% of the alloy). Well-known ferroalloys include ferromanganese, ferrochromium, ferromolybdenum, ferrotitanium, ferrovanadium, ferrosilicon, ferroboron, and ferrophosphorus. Because ferroalloys typically have a lower melting point range than metallic iron, they are often used in the production of steel; because they can be more easily incorporated into molten steel than metallic iron.

[0011] It should be noted that the term "pellets" includes objects commonly referred to as pellets, rods, pencils, and / or slugs. Pellets typically have a maximum average diameter of 20 mm, more typically 16 mm or 15 mm, a minimum average diameter of 2 mm, especially 5 mm, or an average diameter in the range of 10-12 mm. These objects share the common characteristic of being a consolidated form of material and are differentiated primarily by their size and shape.

[0012] C grade iron fines often agglomerate and the agglomeration step / agglomerate formation provides a fine that is more pelletizable. Agglomeration is aided by the presence of a binder. The agglomerates are significantly easier to handle than C grade iron fines, allowing them to be easily transported and fed to furnaces. Additionally, the associated environmental hazards from handling fine particles and particulates are also eliminated. Prior to agglomeration, C grade iron fines generally have an average particle size that is within the range of 50 μm to 10 mm, 500 μm to 6 mm, or 1 mm to 4 mm.

[0013] The binder may include an inorganic binder, an organic binder, or a combination thereof. Typically, the binder is present in the range of 0.3% to 6% by weight, often in the range of 0.5% to 4% by weight, and often in the range of 0.5% to 2.5% by weight.

[0014] In most cases, the inorganic binder (either alone or in combination with one or more organic binders) is present in the range of 1% to 6% by weight, often 2% to 4% by weight.

[0015] In many cases, the inorganic binder comprises one or more silicates (e.g., silicates in the form of their sodium salts) or resistant materials, including, but not limited to, oxides, carbides, or nitrides of silicon, aluminum, magnesium, calcium, and zirconium. For example, the resistant materials may include alumina, fireclay, bauxite, chromite, dolomite, magnesite, silicon carbide, zirconia, or combinations thereof. As used herein, the term "resistant material" refers to a material that is resistant to thermal stress, high pressure, or attack by chemical reagents. The one or more silicates may be in liquid form, powder form, or combinations thereof. If the one or more silicates are in liquid form, they will be present in greater amounts; because of the lower activity level of liquid silicates than powdered silicates. If the one or more silicates are in liquid form, they are often present in the range of 2% to 6% by weight, often 3% to 5% by weight. When one or more silicates are in powder form, they are often present in the range of 0.5% to 3.5% by weight, often 1% to 3% by weight. Two or more silicates may be present, at least one in liquid form and at least one in powder form. When two or more silicates are present, at least one in liquid form and at least one in powder form, the liquid form and the powder form are often present in a ratio of 5:1 to 1:1. Optionally, the ratio may be 3:1, and optionally, the ratio may be 3:2.

[0016] The inorganic binder may further include one or more additives that interact with the binder to promote the cohesion of the c-grade fine powder. Examples of additives include, but are not limited to, glycerol acetate (such as diacetyl glycerol and triacetal glycerol), glycerol, glyoxal, or combinations thereof. In many cases, the additive is triacetal glycerol. Without being bound by theory, the triacetal glycerol chemically interacts with the inorganic binder to aid in the cohesion of the c-grade fine powder.

[0017] In many cases, the organic binder is a polymeric organic binder, which may be selected from organic resins such as polyacrylamide resins, phenol-formaldehyde resins (such as resole resins or novolac resins), and / or polysaccharides (such as starch, hydroxyethyl methylcellulose (MHEC), gum arabic, guar gum, or xanthan gum). Polysaccharides may be used as thickeners. Hydroxyethyl methylcellulose (MHEC) in particular has been found to have good shelf life and to increase strength. It may be mixed with the organic resin.

[0018] Examples of starches include, for example, wheat, corn, and barley starch. More typically, the starch is potato starch because it is relatively inexpensive. Resoles are base-catalyzed phenol-formaldehyde resins in which the molar ratio of formaldehyde to phenol is greater than 1 (usually about 1.5). Novolacs are phenol-formaldehyde resins in which the molar ratio of formaldehyde to phenol is less than 1.

[0019] When a phenol formaldehyde resin is present in combination with at least one inorganic and / or organic binder, it is often present in the range of 0.1% to 0.5% by weight, often 0.2% to 0.4% by weight.

[0020] The organic binder may be present in the range of 3000-16000 mPa·s, often in the range of 6000-14000 mPa·s, or in the range of 10000-12000 mPa·s, and in some cases at about 12000 mPa·s. It has been found that in these ranges the binder provides optimum pellet strength.

[0021] The polymeric organic binder will often comprise polyvinyl alcohol. Polyvinyl alcohol (PVA) may be used as a binder instead of or in addition to other binders, whereby the polymeric organic binder may comprise 10-100% by weight, often 20-90% or 50-75% by weight, of PVA. There may be cases where the binder comprises PVA and a phenol-formaldehyde resin. Alternatively, the polymeric organic binder may consist essentially of PVA or may consist of PVA.

[0022] Without being bound by theory, it is believed that PVA provides fast curing and high strength because the polymer network formed by PVA is strong. Additionally, the process of briquetting with PVA excludes air from the bulk material, which may reduce oxidation of the metal, which is undesirable for the simple reason that it reduces the amount of metallic iron that can be processed by the end user.

[0023] Polyvinyl alcohol is typically formed commercially from polyvinyl acetate by reacting the polyvinyl acetate with sodium hydroxide to replace the acetate radicals of the acetic acid with hydroxyl radicals in a process called saponification. Partial saponification means that some of the acetate groups have been replaced by hydroxyl groups, thereby forming an at least partially saponified polyvinyl alcohol residue.

[0024] Typically, the PVA has a degree of saponification of at least 80%, typically at least 85%, at least 90%, at least 95%, at least 99% or 100% saponification. PVA can be obtained commercially, for example, from Kuraray Europe GmbH, Germany. Typically, it is utilized as an aqueous solution. PVA can be modified, for example, to include sodium hydroxide.

[0025] Typically, the PVA binder, when in solution, has an active polymer content of 12-13% and a pH in the range of 4-7. Further, the PVA will often be of a molecular weight in the range of 15,000-150,000. Optionally, the PVA will often be of a molecular weight in the range of 30,000-120,000. Without being bound by theory, it is believed that using a lower molecular weight, for example, in the range of 15,000-60,000, can produce a more concentrated binder solution, which in turn can improve the strength of the pellets.

[0026] The organic binder (either alone or in combination with one or more inorganic binders) may be present in the range of 0.3-0.9 wt.% of the pellet. It is often in the range of 0.6-0.9 wt.%. It has been found that when less than 0.3 wt.% of the organic binder is present, the structural integrity of the aggregates is low. Without being bound by theory, it is believed that this is due to the poorly packed shape of the C-grade iron fines, resulting in large voids between the fine particles. Thus, the organic binder does not act to form a dispersed film on the surface of the fine particles that simply tries to glue adjacent particles together, as is typical of the mechanism of action of organic binder materials. Instead, the organic binder must form a matrix into which the C-grade iron fines are incorporated. As a result, more organic binder is required than would be typical. This problem is further exacerbated by the fact that the highly metallic regions of the C-grade iron fines do not form strong bonds with the organic binder. At less than 0.3 wt. % of organic binder, the matrix may function to agglomerate the C-grade iron fines, but the structural integrity is weak. In addition, it has been noted that high amounts of glassy elements are present in the C-grade iron fines (due to the high slag content typically found). Furthermore, for treated C-grade iron fines (e.g., when the amount of metallic iron and / or ferroalloy iron exceeds 50 wt. % of the fines), as the metal concentration increases, the metal begins to take on the shape of ball bearings, and the physical characteristics of the ball bearing surfaces are smooth as opposed to irregular (e.g., as in the case of low metallicity C-grade iron fines, which may have a high amount of iron ore). This makes the treated C-grade iron fines less agglomerated, requiring more organic binder than would typically be the case.

[0027] Furthermore, it has been found that if more than 1.0 wt. % organic binder is present, it may be too wet and produce sticky pellets, which is undesirable, in part because of the high density of C grade iron fines, which are not particularly absorbent.

[0028] Thus, while it is possible to form aggregates and pellets having relatively high and relatively low amounts of organic binder, in the general case the organic binder will be present in the range of 0.3-0.9% by weight of the pellet, often in the range of 0.3-0.6% by weight.

[0029] Typically, no clay binder is added to C grade iron fines. The incorporation of such additional binders would reduce the purity of the briquette and decrease its commercial value.

[0030] The pellets also typically include a stabilizer, where the stabilizer is optionally selected from cellulosic organic materials or plant-based gums. Typically, the stabilizer is selected from hydroxyethylmethylcellulose, carboxymethylcellulose (CMC), or guar gum. Typically, the stabilizer includes hydroxyethylmethylcellulose (MHEC) or carboxymethylcellulose (CMC). When present, the pellets will typically include 0.05-0.5% by weight, often in the range of 0.1-0.4% by weight, often in the range of 0.25-0.35% by weight of the stabilizer. The stabilizer may promote the mixing of the C-grade iron fines in the pellets. Because the C-grade iron fines have a high density (e.g., they have a higher density than scrap metal), it may be useful to stabilize the system during the formation of the binder matrix, ensuring that the C-grade iron fines remain well mixed in the binder.

[0031] The applicant has found that the strength and resilience of briquettes made using the first aspect of the invention may be further improved by the addition of a suitable cross-linking agent. Suitable cross-linking agents include, for example, glutaraldehyde, for example at 0.01-5% by weight. Sodium hydroxide may also be used as a cross-linking agent, for example at 0.1% by weight. Cross-linking agents particularly suitable for use with PVA binders include glyoxal, glyoxal resins, PAAE resins (polyamidoamine epichlorohydrin), melamine formaldehyde, organic titanates (e.g. Tizor TM Examples of crosslinkers include dimethyl ether (DuPont), boric acid, ammonium, zirconium carbonate, and sodium glutaric dialdehyde-bis-sulfate. Typically, the crosslinker will be present in an amount of up to 5% by weight, more typically 3% or 2% by weight. If the binder is PVA, this allows, for example, the amount of PVA to be reduced from, for example, 0.8% or 0.5% by weight to, for example, 0.3% or 0.4% by weight PVA. This is a cost-effective way of improving the strength of the material.

[0032] Waterproofing agents may be used to increase the weather resistance of the pellet material. These may be combined with C-grade iron fines or may be combined as a layer on the outer surface of the pellet, such as by spraying. These include, for example, styrene-acrylate copolymers, and bitumen emulsions.

[0033] However, it is possible that the pellets consist or consist essentially of C grade iron fines and a binder.

[0034] In a second aspect of the invention, there is provided a method of making pellets according to the first aspect of the invention, the method comprising mixing C grade iron fines and a binder to form a mixture, and optionally agglomerating the mixture to form pellets. As mentioned above, agglomeration is typically achieved through the formation of a binder matrix between the individual C grade iron fine particles. Agglomeration is further promoted by consolidation of the mixture. This may be vacuum consolidation, extrusion or pressing of the mixture. Consolidation promotes the interaction of the binder with the C grade iron fines. Typically, a pan mixer is used to agglomerate the mixture.

[0035] The pellets may be cold-formed, e.g., without sintering or heating above 60°C or 40°C or 30°C, before being processed (e.g., during steel processing) to extract the metal. In other words, the pellets will often not be intentionally heated during formation, but frictional heat may be generated by any pressing and / or extrusion process used to aid in the formation of the pellets, and the binder may undergo an exothermic reaction in situ. However, none of these heat sources would be expected to generate enough heat to affect the formation of the pellets. The advantages of cold-forming are significant; no heating is required, so there is no energy consumption. Also, no furnaces are required to create the pellets, resulting in a simpler, more economical and environmentally beneficial manufacturing process. Alternatively, a low level of heating may be applied, such as heating in the range of 100°C to 250°C. A low level of heating allows for faster formation of the pellets. If a low level of heating is applied, it is applied for a period of 30 minutes to 24 hours. Those skilled in the art will understand and appreciate that factors such as the external ambient temperature, the nature of the ingredients in the formulation, and the desired characteristics of the resulting pellets (e.g., low moisture content) will affect the duration for which low level heat is applied, and therefore, those skilled in the art will consider such factors when determining the duration and level of heat to apply in their process.

[0036] In a third aspect of the invention there is provided a method for producing steel comprising heating pellets according to the first aspect of the invention in a furnace, such as an electric arc furnace. The use of an electric arc furnace, as opposed to a blast furnace, results in a system which can utilise the flexibility of an electric arc furnace.

[0037] Typically, the pellets are heated in an oxidizing atmosphere, typically oxygen is applied so that carbon and contaminants are oxidized from the iron present in the C grade iron fines.

[0038] The invention also provides a method for producing steel, comprising providing pellets according to the invention, optionally produced by a method for producing pellets according to the invention, transporting the pellets to an electric arc furnace and producing steel by a method of the invention.

[0039] The pellets may be produced at a location separate from where they are used, i.e., they may be manufactured at a location where, for example, iron ore fines are deposited, processed into pellets by combining with a binder, and then transported to an electric arc furnace at a geographically distant location, for example by ship, road, or rail.

[0040] Alternatively, the binder may be mixed with the particulate iron ore substantially in the same location as the furnace and then charged into the furnace.

[0041] The pellets may be loaded into the furnace, for example, by a conveyor belt or by other suitable means for moving the pellets.

[0042] Thus, there is provided a pellet comprising C grade iron fines, optionally comprising iron and / or ferroalloys in the range of 50-95% by weight of the C grade fines, and a binder, the binder comprising an inorganic binder, an organic binder, or a combination thereof. Optionally, the binder is 0.3% to 6% by weight of the pellet. Optionally, the inorganic binder (either alone or in combination with one or more organic binders) is 1% to 6% by weight of the pellet. Optionally, the organic binder (either alone or in combination with one or more inorganic binders) is 0.3 to 0.9% by weight of the pellet, optionally 0.3 to 0.5% by weight. Optionally, the C-grade iron fines have an average particle size in the range of 20 μm to 8 mm, and the binder optionally comprises polyvinyl alcohol, with a molecular weight in the range of 15,000 to 150,000 and a viscosity in the range of 3000 to 16,000 mPa·s. Optionally, the binder further comprises a phenol formaldehyde resin in combination with at least one inorganic and / or organic binder, often present in the range of 0.1% to 0.5% by weight, often 0.2% to 0.4% by weight. Optionally, the pellet further comprises 0.05 to 0.5% by weight of a stabilizer, where the stabilizer is optionally selected from a cellulosic organic material or a plant-based gum. Typically, the stabilizer is selected from hydroxyethyl methylcellulose, carboxymethylcellulose, or guar gum. Typically, the stabilizer comprises hydroxyethyl methylcellulose or carboxymethylcellulose.

[0043] Further provided is a method for producing the cold formed pellets as described, comprising mixing C grade iron fines and a binder to form a mixture, and optionally agglomerating the mixture by the formation of a binder matrix to form pellets.

[0044] There is further provided a method for making the described pellets, comprising mixing C-grade iron fines and a binder to form a mixture, optionally agglomerating by forming a binder matrix, and applying low-level heat, typically in the range of 100°C to 250°C, to the mixture to form pellets. When low-level heat is applied, it is applied for a period of 30 minutes to 24 hours. As noted above, one skilled in the art will understand and appreciate that factors such as the external ambient temperature, the nature of the ingredients in the formulation, and the desired characteristics of the resulting pellets (e.g., low moisture content) will affect the duration for which low-level heat is applied. Thus, one skilled in the art will consider such factors when determining the duration and level of heat to apply in a process.

[0045] Additionally, there is provided a method for producing steel comprising heating the described pellets in an electric arc furnace, optionally under an oxidizing atmosphere. Also provided is a method for producing steel comprising providing the described pellets, optionally produced by the method, transporting the pellets to an electric arc furnace, and producing steel by the method.

[0046] Unless otherwise specified, each recited integer may be used in combination with any other integer, as would be understood by one of ordinary skill in the art. Furthermore, it is specifically contemplated that, although all aspects of the present invention preferably "comprise" the features recited in connection with that aspect, they may "consist of" or "consist essentially of" the generally recited features. Additionally, all terms are intended to be given their commonly understood meanings in the art, unless specifically defined herein.

[0047] Furthermore, in the discussion of the present invention, unless stated to the contrary, the disclosure of alternative values ​​for the upper or lower limits of a parameter's acceptable range will be construed as implicitly indicating that each intermediate value of said parameter between the lower and higher alternative values ​​is itself also disclosed as a possible value for the parameter.

[0048] Additionally, unless otherwise noted, all numerical values ​​set forth herein are understood to be modified by the term "about."

[0049] In order that the present invention may be more readily understood, it will now be further explained with reference to specific examples. EXAMPLES

[0050] Example 1 - Evaluation of binder functionality with respect to viscosity and molecular weight

[0051] (i) Viscosity was measured using a LAMY B-one viscometer at 50 rpm. All grades of PVA were purchased from Kuraray®.

[0052] [Table 1]

[0053] Test specimens were prepared using high metallization ferronickel substrate with ferroalloy content of about 72% at standard loading rates and loading conditions. Stabilizing binders were incorporated into the formulation. The metal content of C-fine powder may be increased using multi-phase physical separation techniques such as crushing, grinding, dry jigging, wet jigging, magnetic separation, and wet high-intensity magnetic separation, thus producing the high metallization ferronickel and iron substrates of the examples.

[0054] (ii)

[0055] [Table 2]

[0056] It has been observed that a viscosity above 3000 mPa·s, and ideally at least 6000 mPa·s, is desirable for both green strength (ie, pellet formation) and cured strength.

[0057] It has been determined that a viscosity of 3000-6000 mPa·s will give good cured strength, but green strength may be compromised on a production scale, although other ingredients may be added to modify the formulation.

[0058] Viscosities below 3000 mPa·s have been found to be unsatisfactory.

[0059] Example 2: Effect of stabilizers on the formulation

[0060] Iron C fines was mixed with three different binder formulations and briquettes of 20 mm x 30 mm x 40 mm were made in a HUTT roller press at 210 bar pressure and gravity fed.

[0061] [Table 3]

[0062] From a comparison of formulations 1 and 2, it can be seen that the presence of cellulose fiber stabilizer improves the set strength of the pellets. A comparison of formulations 2 and 3, and formulations 3 and 4 shows that increasing the amount of binder and stabilizer also improves the set strength of the pellets. The briquettes had an iron content of about 85%.

[0063] Example 3: Further Examples

[0064] Ferronickel fines were mixed with two binder formulations and made into briquettes:

[0065] [Table 4]

[0066] Example 4: Vibro-compacted specimens

[0067] Iron C fine powder and ferronickel samples were prepared by vibro tamping method:

[0068] Two samples were produced by mixing each material in a direct acting pan mixer and placed into 150mm x 150mm concrete test moulds. No release agent was used. The moulds were filled in one layer and compacted for 10 seconds using a reciprocating electric hammer drill. To ensure uniform application of force, a 148mm 2 Plates were used.

[0069] The specimens were free to separate from the mold in the green state.

[0070] The green samples, when tested in a concrete load tester, provided strengths as shown below, indicating that this is a useful pelletizing method: Ferronickel: 14.5N / mm 2 Iron: 6.1N / mm 2

[0071] Example 5 – Particle size distribution of various C fines or iron-containing compounds

[0072] [Table 5]

[0073] Particle size distribution was measured using BS EN 933-1:2012.

[0074] Example 6 – Inorganic Binder System

[0075] Iron C fines were mixed with four different inorganic binder formulations and briquettes were made in a HUTT roller press at 210 Bar pressure and gravity fed.

[0076] [Table 6]

[0077] This table shows that when a combination of liquid and powdered silicates is present, good compressive strength and handling properties can be obtained.

[0078] C-grade iron fines are often in the form of rounded particles (high sphericity) with a narrow particle size distribution, making it difficult to achieve strong agglomerations; because of the low level of mechanical interlocking within the fines matrix. However, as is evident from Table 6, the above inorganic binder system results in pellets with both high green strength and high cured compressive strength.

[0079] It will be appreciated that the products and processes of the present invention can be embodied in a variety of ways, only a few of which have been illustrated and described above.

Claims

1. A pellet comprising C grade iron fines and a binder.

2. 2. The pellet of claim 1, wherein the C grade iron fines comprises in the range of 50-95% by weight of iron and / or ferroalloys.

3. 3. The pellets according to claim 1 or claim 2, wherein the C grade iron fines have a particle size distribution in the range of 50 μm to 8 mm.

4. The pellet of any one of claims 1 to 3, wherein the binder comprises an inorganic binder, an organic binder, or a combination thereof.

5. A pellet according to any one of claims 1 to 4, wherein the organic binder is present in the range of 0.3 to 0.5% by weight of the pellet.

6. A pellet according to any one of claims 1 to 5, wherein the inorganic binder is present in the range of 1% to 6% by weight.

7. The pellet according to any one of claims 1 to 6, wherein the organic binder has a viscosity in the range of 3,000 to 16,000 MPa·s.

8. The pellet according to any one of claims 1 to 7, wherein the binder comprises an inorganic binder comprising two or more silicates, the two or more silicates comprising at least one silicate in liquid form and at least one silicate in powder form.

9. The pellet of any one of claims 1 to 8, wherein the binder comprises a polymeric organic binder selected from polyacrylamide resins, resole resins, novolac resins, polyvinyl alcohol, and polysaccharides.

10. The pellet of any one of claims 1 to 9, wherein the binder comprises polyvinyl alcohol.

11. The pellets of claim 10, wherein the polyvinyl alcohol has a molecular weight in the range of 15,000 to 150,000.

12. The pellet of claim 10 or claim 11, wherein the binder further comprises a phenol-formaldehyde resin.

13. A pellet according to any one of claims 1 to 12, further comprising a stabilizer.

14. 14. The pellet of claim 13, wherein the stabilizer is selected from cellulosic materials.

15. A pellet according to claim 13 or claim 14, comprising 0.05 to 0.5% by weight of a stabilizer.

16. The pellet of any one of claims 1 to 15, further comprising a cross-linking agent.

17. 17. A method for producing pellets according to any one of claims 1 to 16, comprising mixing the C grade iron fines and the binder to form a mixture, and agglomerating the mixture to form pellets.

18. 20. The method of claim 17, wherein the pellets are cold formed.

19. 19. The method of claim 17 or claim 18, wherein the aggregation comprises the formation of a binder matrix.

20. The method of any one of claims 17 to 19, wherein agglomeration comprises compaction of the mixture.

21. A method for producing steel comprising heating a pellet according to any one of claims 1 to 16 in an electric arc furnace.

22. 22. The method of claim 21, wherein the pellets are heated in an oxidizing atmosphere.

23. 23. A method for producing steel comprising providing pellets according to any one of claims 1 to 16, optionally produced by a method according to any one of claims 17 to 20, transporting the pellets to an electric arc furnace, and producing steel by a method according to claim 21 or 22.